A Critical Review of the Bacterial Baptism Hypothesis and the Impact of Cesarean Delivery on the Infant Microbiome - Stinson, Lisa F.; Payne, Matthew S.; Keelan, Jeffrey A. (Frontiers in Medicine, 2018)
Infants delivered by Caesarean section are at a greater risk of non-communicable diseases than their vaginally-delivered counterparts. In particular, epidemiological studies have linked Caesarean delivery with increased rates of asthma, allergies, autoimmune disorders, and obesity. Mode of delivery has also been associated with differences in the infant microbiome. It has been suggested that these differences are attributable to the “bacterial baptism” of vaginal birth, which is bypassed in Caesarean deliveries, and that the abnormal establishment of the early life microbiome is the mediator of later-life adverse outcomes observed in Caesarean delivered infants. In this review we summarise and critically appraise the current evidence for a causal association between Caesarean delivery and neonatal dysbiosis. We suggest that, while Caesarean delivery is certainly associated with alterations in the infant microbiome, the lack of exposure to vaginal microbiota is not a major contributing factor. Instead, it is likely that indication for Caesarean delivery, intrapartum antibiotic administration, absence of labour, differences in breastfeeding behaviours, maternal obesity, and gestational age are major drivers of the Caesarean delivery microbial phenotype. In light of this information, we call into question the rationale for the increasingly popular process of “vaginal seeding” and support calls for the halting of this practice until robust evidence of need, efficacy and safety is available.